NEW EXPERIMENTAL PATHOGENETICALLY GROUNDED VARICOCELE MODE - M. A. Berdnikov; N. V. Antipov; Yu. K. Gulkov (Кубанский научный медицинский вестник, 2018)
Aim. The main aim of the study was to develop a pathogenetically grounded varicocele model and to compare it with the well-known one.Materials and methods. 30 male mongrel laboratory rats were divided in 3 equal groups, in the 1st group Saypol technique was performed, in the 2nd – one-time partial ligation of both spermatic cords with following testicles abdominisation. The 3rd group was the control one. There was a gonadectomy with following histological investigation on the 7th, 15th and 30th days. Results. Group 1 was presented with adhesions in abdominal cavity and hydronephrosis in all rats. The changes in the spermatic veins and testicles were reached both in the 1st and 2nd groups with more signifi ones in the 2nd group by the 15th day. There were phlebectasia, tunica media thinning, infl infi of the testicles with spermatogenous epithelium and mature germ cells necrobiosis, in some cases also arterial vessels proliferation and even spermatogenesis recovery.Conclusion. Thereby, the use of the suggested technique is more grounded from the technical, economical and pathogenetic points of view.